A bio-inspired exploration of eco-friendly bael gum and guar gum-based bioadhesive as tackifiers for packaging applications. (October 2021) - Sharma, Bhasha; Sandilya, Avinash; Patel, Urvee; Shukla, Anurag; Sadhu, Susmita Dey
Abstract: The potential opportunities for synthetic adhesives have increased abruptly due to the variety of strengths provided by them. These adhesives release toxic fumes, such as formaldehyde which is a serious predicament. To annihilate this issue, the stipulation for the burgeoning of biodegradable packaging materials has come into account. The objective of this work is to prepare a biobased, biorenewable, and biodegradable cloth-to-cloth, cloth-to-paper, and paper-to-paper adhesive using natural ingredients. The effects of guar gum and bael gums as tackifiers were studied individually as well as synergistically. Neem and olive oil were used as preservatives to impart antimicrobial properties. The performance and stability of adhesive have been determined at ambient as well as extended conditions. The mechanical peel strength and biodegradation analysis have been carried out. The effect of time and temperature on viscosity of guar gum (18%) has been found highest in contrary to other samples. The mechanical peel strength of adhesives by immersing resultant samples in different solvent media has been investigated. The resultant adhesive has been found superior to be utilized in multilayered films, paper binding and cloth reinforced paper bags. Graphical abstract: Graphical illustration of biorenewable and biodegradable cloth-to-cloth, cloth-to-paper and paper-to-paper bio-adhesive using natural ingredients like neem oil, clove oil and guar gum and bael gum as tackifiers grafted into PVA and gelatin for packaging applications. Image 1 Highlights: Fabrication of biodegradable, biorenewable adhesive for packaging applications. The effects of guar gum and bael gums as tackifiers were studied individually as well as synergistically. Neem and olive oil were used as preservatives to impart antimicrobial properties. The effect of time and temperature on viscosity of guar gum (18%) has been found highest in contrary to other samples.